Sublethal toxicity test of mercury (Hg) in the flesh and tissue of Tilapia (Oreochromis niloticus) - Yusnaini Yusnaini; Emiyarti Emiyarti; Indriyani Nur; Oce Astuti; Rahmad Sofyan Patadjai (Journal Omni-Akuatika, 2020)
This study tested the sublethal toxicity of mercury (Hg) in the flesh and tissue of tilapia (Oreochromis niloticus). This research used an experimental method completely randomized design (CRD) with 3 treatments and 3 replications. The treatments used different Hg concentrations: Treatment A = 0.08 ppm; B = 0.16 ppm; C = 0.24 ppm; and the control group = without the addition of Hg. The parameters observed were the accumulation of mercury (Hg) in the flesh and tissue damage (histopathology) of the gills, kidneys and liver of tilapia. The results showed that the highest Hg accumulation was at the highest Hg concentration (treatment C = 0.24 ppm). Tissue damage was mainly found in the kidneys, liver and gills of fish exposed to Hg with indications of bleeding, tubular necrosis, vacuolization of epithelial cells, and mononuclear cell infiltration. The results showed that the toxicity of mercury to the organs increased with the increase in the concentration of Hg in water. Keywords : flesh, mercury, Oreochromis niloticus, sublethal, tissue